2021
DOI: 10.1016/j.ajpc.2021.100294
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lipid-lowering medications on coronary artery plaque characteristics

Abstract: Atherosclerosis is the predominant cause of coronary artery disease. The last several decades have witnessed significant advances in lipid-lowering therapies, which comprise a central component of atherosclerotic cardiovascular disease prevention. In addition to cardiovascular risk reduction with dyslipidemia management, some lipid-based therapies show promise at the level of the atherosclerotic plaque itself through mechanisms governing lipid accumulation, plaque stability, local inflammation, endothelial dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…Although the authors did not observe differences in plaque composition between the two treatment groups, they observed an inverse correlation between changes in LDL cholesterol levels and plaque calcification (r = 0–15; p < 0.001). The same observation was made in statin studies where statin treatment was associated with an increase in plaque calcification [ 34 , 70 , 71 ]. Thus, it is suggested that plaque calcification may be due to lipid-lowering effects and not due to the pleiotropic properties of statins.…”
Section: Statinssupporting
confidence: 58%
See 1 more Smart Citation
“…Although the authors did not observe differences in plaque composition between the two treatment groups, they observed an inverse correlation between changes in LDL cholesterol levels and plaque calcification (r = 0–15; p < 0.001). The same observation was made in statin studies where statin treatment was associated with an increase in plaque calcification [ 34 , 70 , 71 ]. Thus, it is suggested that plaque calcification may be due to lipid-lowering effects and not due to the pleiotropic properties of statins.…”
Section: Statinssupporting
confidence: 58%
“…High-intensity statin treatment may reduce LDL levels by up to 50%. Statins have pleiotropic effects that include the inhibition of oxidation-sensitive inflammatory pathways, the modulation of leukocyte–endothelial cell interactions, and the reduction of inflammatory cytokine levels [ 33 , 34 , 35 ]. Statin therapy clearly reduces the risk of MACEs in patients with CVD [ 27 , 36 , 37 ].…”
Section: Statinsmentioning
confidence: 99%
“…Atherosclerotic cardiovascular disease is one of the leading causes of death worldwide [ 92 ]. Despite the development of lipid-lowering strategies to help stabilize high-risk atherosclerosis, the risk of the disease remains significant [ 93 ]. Detecting inflamed plaque is challenging.…”
Section: Pdt Mechanism Of Actionmentioning
confidence: 99%
“…Plaque calcification, a process characterized by the deposition of calcium within atherosclerotic plaques, has been a subject of interest and investigation in cardiovascular research [32] . The paradox observed with statins, a class of drugs commonly used to reduce cholesterol and stabilize plaques, lies in their potential to promote both regression and calcification of plaques [33] . Statins effectively lower LDL cholesterol levels, reduce inflammation, and improve plaque stability, which generally lead to plaque regression [34] .…”
Section: Physical Activitymentioning
confidence: 99%